The Problem of Syntactic Isoglosses in G. Jahukyan’s Comparative Studies - Gabrielyan, Yuri (Bulletin of Yerevan University B: Philology, 2021)
The paper examines G. Jahukyan’s viewpoint on syntactic isoglosses among the Indo-European languages and particularly between Armenian and the Celtic languages. In his studies, the scientist puts forward the hypothesis of the VSO typological sample as being more archaic, which, however, is not definitely evaluated in Indo-European linguistics. The author of this paper confirms G. Jahukyan’s viewpoint on the above-discussed matter with the help of careful examination of appropriate facts and also the results of his researches.